Learners and EHRs: A path forward. Issue 4 (25th November 2022) - Bell, Amanda; Chung, Han‐Oh
Abstract : Effective EHR utilization requires organizational culture transformation, leading to suggestions that learners be included early in EHR transitions for successful implementation, effective use, and future benefits.